Case report – Solitary finger nail bed neurofibroma (Indian Journal of Case Reports, 2026)
Neurofibromas arise along a nerve fiber and usually involve nerves in or near the skin. They rarely develop in the hand and fingers. Nail bed solitary neurofibroma is an exceptionally rare event with no more than eight cases described in the literature. We present the case of a 39-year-old female patient with a lesion located in the radial side of the nail bed of the right-hand index finger. These tumors are slow-growing and rarely painful. Imaging tools are not very helpful in making the diagnosis. Final diagnosis rests on histopathology. No case of nail bed solitary neurofibroma showed recurrence. Complete surgical excision should be considered a diagnostic and therapeutic procedure.